Hydrodynamic Evaluations of Four Mock Femoral Venous Cannulas - Şahin,Türker (2018)
Abstract Objective: To report the results of four mock femoral venous cannulas and the hydrodynamical superiority of one of them, which is the completely punched (CP) model, upon the other three. Methods: Four simulated femoral venous cannulas (single-stage, two-stage, multi-stage, and CP model) were designed from a 1/4” x 1/16” x 68 cm polyvinyl chloride (PVC) tubing line for testing. Holes on the PVC tubes were opened by a 5 mm aortic punch. In order to evaluate the cannulas' drainage performance, gelofusine was used as fluid. The fluid was drained for 60 seconds by gravitation and then measured for each model separately. Results: Mean drained volumes of single-stage, two-stage, and multi-stage cannulas were 2.483, 2.561, and 2.603 mL, respectively. However, the CP cannula provided us a mean drained volume of 2.988 mL. There were signiﬁcant differences among the variables of the CP cannula and the other three mock cannulas concerning the drained fluid flow (P<0.01). Conclusion: In our study, the measured mean volumes showed us that more drainage surface area provides better fluid drainage.